2016
DOI: 10.1093/jamia/ocv214
|View full text |Cite
|
Sign up to set email alerts
|

Sociocultural variation in attitudes toward use of genetic information and participation in genetic research by race in the United States: implications for precision medicine

Abstract: Background “Precision medicine” (PM) requires researchers to identify actionable genetic risks and for clinicians to interpret genetic testing results to patients. Whether PM will equally benefit all populations or exacerbate existing disparities is uncertain.Methods We ascertained attitudes toward genetic testing and genetic research by race in the United States using the online Amazon mTurk US workforce (n = 403 White; n = 56 African American (AA)). Generalized linear models were used to test differences in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 50 publications
(36 reference statements)
0
17
0
Order By: Relevance
“…Additional limitations of our study involve our respondent characteristics and small sample size. We did not obtain information on respondents’ race or ethnicity, which may influence attitudes toward genetic testing [ 40 ]. Respondents in our study were relatively well-educated and had higher socio-economic status than the United States general population [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additional limitations of our study involve our respondent characteristics and small sample size. We did not obtain information on respondents’ race or ethnicity, which may influence attitudes toward genetic testing [ 40 ]. Respondents in our study were relatively well-educated and had higher socio-economic status than the United States general population [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Less favorable views about the value of research predicted a lower willingness to participate in research (Bloss et al, 2018). Importantly, while some studies reported a correlation between being a member of a racial/ethnic minority group (Hispanic, African American, or Asian American) and decreased willingness to participate (n = 5; Aagaard-Tillery et al, 2006;Bloss et al, 2018;Dye et al, 2016;Hensley Alford et al, 2011;Sanderson et al, 2017), other studies found that race and ethnicity were not predictors of consent for research…”
Section: Subtheme C: Predictors Of Participationmentioning
confidence: 99%
“…Dimensions underlying genomic research (e.g. participation) are not equally accepted by all populations and understanding these elements could ensure equal benefit from precision medicine research [5]. The objective of this article is to describe the likelihood of respondents from a high and a low-middle income country to participate in genetic research and to identify commonalities across these two countries.…”
Section: Introductionmentioning
confidence: 99%